2003
DOI: 10.1074/jbc.m207943200
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Ras Leads to Rho Activation by Activating the Mitogen-activated Protein Kinase Pathway and Decreasing Rho-GTPase-activating Protein Activity

Abstract: Transformation by oncogenic Ras requires signaling through Rho family proteins including RhoA, but the mechanism(s) whereby oncogenic Ras regulates the activity of RhoA is (are) unknown. We examined the effect of Ras on RhoA activity in NIH 3T3 cells either stably transfected with H-Ras(V12) under control of an inducible promoter or transiently expressing the activated H-Ras. Using a novel method to quantitate enzymatically the GTP bound to Rho, we found that expression of the oncogenic Ras increased Rho activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 71 publications
11
56
1
Order By: Relevance
“…Activation of ERK1/2 during periods of Rho family inhibition, although not widely reported, has been described. Decreases in the GTP-bound forms of Rac1 and Cdc42 are associated with ERK activation in fibroblasts (48), RhoB inhibits constitutive activation of ERK in tumor cells (49), and inhibition of RhoA stimulates ERK in MCF-7 breast cancer cells (50). Particularly relevant to the present results, a recent study found that inhibition of Rho up-regulated TNF-␣ in macrophages and that this effect was mediated by ERK1/2 activation (43).…”
Section: Discussionsupporting
confidence: 55%
“…Activation of ERK1/2 during periods of Rho family inhibition, although not widely reported, has been described. Decreases in the GTP-bound forms of Rac1 and Cdc42 are associated with ERK activation in fibroblasts (48), RhoB inhibits constitutive activation of ERK in tumor cells (49), and inhibition of RhoA stimulates ERK in MCF-7 breast cancer cells (50). Particularly relevant to the present results, a recent study found that inhibition of Rho up-regulated TNF-␣ in macrophages and that this effect was mediated by ERK1/2 activation (43).…”
Section: Discussionsupporting
confidence: 55%
“…Thus, active H-Ras might abrogate checkpoints sensing anchorage and/or cytoskeletal organization in addition to promoting cell proliferation. One mediator of H-Ras-induced cytoskeletal rearrangements is RhoA, which is activated upon overexpression of activated H-Ras (27,28). RhoA is also the only member of the Rhoprotein family of small GTPases that is required for cytokinesis in mammalian cells (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Rho standards were purified from bacteria to >90% homogeneity as judged by PAGE/Coomassie staining, and were quantified by comparison to bovine serum albumin. Glutathione-S-transferase(GST)-tagged rhotekin Rho binding domain (RBD) was purified from bacteria as described previously [3,17]. Vectors encoding Rho A and B with the N-terminal epitope tag EEEEYMPME (EE-tag) were constructed as described [18]; vectors encoding hemagglutinin (HA)-tagged RhoC (wild type and V14) were purchased from the University of Misouri-Rolla cDNA Resource Center.…”
Section: Materials and Dna Constructsmentioning
confidence: 99%
“…To determine the activation state of each Rho isoform separately, we performed the assay as described by Ren et al [17], assessing the amount of GTP-bound RhoA, B, or C by Western blotting. To quantify absolute amounts of GTP and GTP+GDP bound to Rho, we employed a coupled enzymatic assay using nucleoside diphosphate kinase and luciferase as described previously [3,18].…”
Section: Measurement Of Rho Activationmentioning
confidence: 99%
See 1 more Smart Citation